Towards the scale-up of the formation of nanoparticles on α-Ag2WO4 with bactericidal properties by femtosecond laser irradiation - Assis, Marcelo; Cordoncillo, Eloisa; Torres-Mendieta, Rafael; Beltrán-Mir, Héctor; Mínguez-Vega, Gladys; Oliveira, Regiane; Leite, Edson R.; Foggi, Camila C. [UNESP]; Vergani, Carlos E. [UNESP]; Longo, Elson; Andrés, Juan (Springer Nature, 2018)
In recent years, complex nanocomposites formed by Ag nanoparticles coupled to an α-Ag2WO4 semiconductor network have emerged as promising bactericides, where the semiconductor attracts bacterial agents and Ag nanoparticles neutralize them. However, the production rate of such materials has been limited to transmission electron microscope processing, making it difficult to cross the barrier from basic research to real applications. The interaction between pulsed laser radiation and α-Ag2WO4 has revealed a new processing alternative to scale up the production of the nanocomposite resulting in a 32-fold improvement of bactericidal performance, and at the same time obtaining a new class of spherical AgxWyOz nanoparticles.